Genome-Informed Real-Time Polymerase Chain Reaction for Detection of Erwinia pyrifoliae, the Causal Agent of Asian Pear Blight - Jarred Yasuhara-Bell; Vessela Mavrodieva; Yazmín Rivera (PhytoFrontiers)
Erwinia pyrifoliae causes blight symptoms on pears (Pyrus spp.), apple (Malus spp.), and strawberry (Fragaria × ananassa), with up to 40% losses in strawberry observed during a 2013 outbreak in the Netherlands. These commodities are of economic importance in the United States. Introduction and establishment of E. pyrifoliae could result in huge economic losses, thus creating a need for appropriate surveillance and disease management. The availability of validated diagnostic tools is the cornerstone of successful surveillance, quarantine, and eradication measures. In this study, assays based on two different E. pyrifoliae-specific targets were validated thoroughly. The hrpW target was described previously, whereas the hsvC target was established in this study. Both were duplexed with either a 16S rDNA (bacteria) or 18S rDNA (plant) internal control to accommodate different sample types and extractions. The hrpW and hsvC targets showed similar performance, with a limit of detection of approximately five genome equivalent copies per reaction with 100% positivity, demonstrating high sensitivity. The assays also demonstrated high analytical and diagnostic specificity. Positive results were obtained for eight known E. pyrifoliae isolates, comprising Korean and Japanese isolates, and no cross-reactions were observed with other Erwinia spp. tested, except closely related E. uzenensis, as well as 74 other pathogens and two commercial biocontrol agents. Symptomatic strawberries were found in the United States, and these assays were able to confirm the first report of E. pyrifoliae. These assays were deployed successfully and are beneficial tools that support efforts to protect U.S. agriculture and facilitate safe trade. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.